2021
DOI: 10.1111/liv.14991
|View full text |Cite
|
Sign up to set email alerts
|

Inferior cure rate in pilot study of 4‐week glecaprevir/pibrentasvir treatment with or without ribavirin of chronic hepatitis C

Abstract: Background & Aims Shortening the treatment duration for chronic hepatitis C may increase feasibility and reduce the cost of cure. The aims of this study were to compare 4 weeks of glecaprevir/pibrentasvir (GLE/PIB) treatment with and without ribavirin for patients with chronic hepatitis C and favourable baseline characteristics and to monitor the development of resistance‐associated substitutions (RAS) and re‐treatment outcomes if treatment failed. Methods We performed an open‐label single‐centre randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The reason why viral load was not included in this study design is that we wanted a simple and replicable design that easily could be transferred to clinical practice and especially in resource limited areas where preclinical baseline variables can be difficult to obtain. In addition, baseline viral load was not found to be a predictor of achieving SVR12 in the first phase of the study [ 19 ]. Another approach to reduce treatment duration is response-guided therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason why viral load was not included in this study design is that we wanted a simple and replicable design that easily could be transferred to clinical practice and especially in resource limited areas where preclinical baseline variables can be difficult to obtain. In addition, baseline viral load was not found to be a predictor of achieving SVR12 in the first phase of the study [ 19 ]. Another approach to reduce treatment duration is response-guided therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A REDCAP database served as the electronic case report form (e-CRF) where all clinical data were recorded. Initially patients were seen eight times during the 48-week study period with blood samples at each visit as in the first phase of the study [ 19 ]; see Supplemental Table S1 . An amendment changed this in January 2020 so patients should only be physically present at the first three visits (screening, treatment start and two weeks after treatment start).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study details have recently been reported. 8 In total, 17 received GLE/PIB and 15 patients received GLE/PIB plus ribavirin. Overall, 21 patients achieved SVR and 11 experienced treatment failure.…”
Section: Study Populationmentioning
confidence: 99%
“…HCV is divided into 8 genotypes and >90 subtypes, and unassigned putative subtypes are still being detected, e.g., in Africa ( 2 4 ). By deep sequencing, we investigated an unknown subtype of HCV genotype 1 from a patient participating in the 4RIBC study ( 5 ) (EudraCT no. 2017-005179-21) who had been treated for 4 weeks with glecaprevir and pibrentasvir (Maviret).…”
Section: Announcementmentioning
confidence: 99%